The serve clock reduced rule violations, but did not speed up the game: A closer look at the inter-point time at the 2018 US Open - Mühlberger, A.; Kolbinger, O. (Journal of Human Sport & Exercise, 2021)
After treating time rule violations as a trivial offense over the past, tennis associations in 2018 permanently introduced an on-court serve clock to make sure that players do not exceed the time limit between points. In this study, we investigated the influence of this technological officiating aid at its first use in Grand Slam tennis at the 2018 US Open. By investigating time intervals between 2135 points at the Men`s single tournament we found that the share of rule violations decreased (26.3%), but the average time did not (21.6s) compared to previous studies. We could further confirm that the players still use this time interval for tactical reasons and to recover after longer rallies. In addition, the umpires, which do not show any reputation bias, have a significant influence on the inter-point time as well. Based on these findings we suggest introducing a serve clock that is started automatically. Further, we argue that a dynamic time limit, which takes the intensity of the previous rally into account, would be more appropriate. Players could be granted more time for recovery after longer rallies, but less time after shorter ones in order to reach the intended goals regarding pace of play.